Preoperative magnetic resonance imaging of anal fistulas with scrotal extension: a retrospective study - Vo, Duc Tan; Nguyen, Truc Thi Thuy; Nguyen, Nam Hoang; Nguyen, Linh Thi Thuy; Nguyen, Thien Thi Thanh; Phan, Chien Cong (Frontiers in Surgery, 2023)
This study aimed to elucidate the magnetic resonance (MR) characteristics of anal fistulas extending to the scrotum, and the applicable rules, and to correlate MR features with surgical findings. We conducted a retrospective study in 150 consecutive patients with anal fistulas extending into the scrotum, who were diagnosed and underwent surgery at University Medical Center Ho Chi Minh City between January 2017 and April 2022. MR findings were evaluated and compared with surgical findings using Cohen's kappa coefficient (k) with a 95% confidence interval. 150 patients (mean age 37.6 ± 10.9 years) with 166 fistulas, including 150 anal fistulas with scrotal extension. Most fistulas were low transsphincteric (80.0%, 120/150 patients). There was a strong agreement for primary tract classification and detecting the location of internal openings between MRI and surgical findings with k = 0.83 (0.78-0.87) and k = 0.89 (0.85 -0.93) (p<0.001), respectively. There is a significant correlation between the location of internal openings and the type of fistula (p<0.05). Low transsphincteric fistulas were predominant in the anterior group (103/122 patients vs. 10/19 patients), while in the posterior group, it was more common in the high transsphincteric fistulas (7/19 patients vs. 14/122 patients), and the intersphincteric fistulas (1/19 patients vs. 5/122 patients); and the suprasphincteric fistulas were only seen in the posterior group (1 patient). Anal fistulas with scrotal extension are exceptions to Goodsall's rule. Albeit long-tract fistulas, most are low transsphincteric and have anterior internal openings.